1993
DOI: 10.1212/wnl.43.2.358
|View full text |Cite
|
Sign up to set email alerts
|

2',3'‐Dideoxycytidine (ddC) toxic neuropathy

Abstract: We administered the antiviral agent 2',3'-dideoxycytidine (ddC) to HIV-infected patients with either ARC or AIDS as part of the AIDS Clinical Treatment Group protocol 012 and serially evaluated them with neuropathic symptom questionnaires, neurologic examinations, nerve conduction studies, and quantitative sensory testing (QST). All patients treated with high-dose ddC (0.06 and 0.03 mg/kg every 4 hours) developed a painful, predominantly sensory peripheral neuropathy, with a mean onset of 7.7 weeks, which reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 0 publications
1
79
1
2
Order By: Relevance
“…This has been described with many neurotoxins such as thalidomide, hydrocarbon sniffing with tetraethyl lead, n-hexane (and methyl-n-butyl ketone and 2,5-hexanedione), chemotherapeutic agents, antivirals, and pyridoxine [18][19][20][21][22][23].…”
Section: Case Continuationmentioning
confidence: 95%
“…This has been described with many neurotoxins such as thalidomide, hydrocarbon sniffing with tetraethyl lead, n-hexane (and methyl-n-butyl ketone and 2,5-hexanedione), chemotherapeutic agents, antivirals, and pyridoxine [18][19][20][21][22][23].…”
Section: Case Continuationmentioning
confidence: 95%
“…Elimadi et al, 1997 AZT inhibits NADH oxidase Pereira et al, 1998 AZT treatment has no effect on mitochondria Herzberg et al, 1992 DDC Peripheral nerve Painful peripheral neuropathy in 50 -100% of patients Berger et al, 1993Dubinsky et al, 1989Merigan et al, 1989Yarchoan et al, 1990 Inhibition of mtDNA replication in MOLT cells. Mitochondrial structural changes and lipid accumulation in nerves of DDC-treated rabbits.…”
Section: Mtdna Dna Polymerase-␥ and Nrti Toxicitymentioning
confidence: 99%
“…Doserelated, painful peripheral neuropathies occur in the majority of patients treated with ddC in doses of 0.03 to 0.09 mg/kg/day (Berger et al, 1993;Dubinsky et al, 1989;Merigan et al, 1989;Yarchoan et al, 1990). Peripheral neuropathy with ddI was unexpected, based upon preclinical data .…”
Section: Toxicity From Other Nrtis: Varying Tissue Targetsmentioning
confidence: 99%
“…4,7 Dideoxynucleoside antiretrovirals (d-drug ARV) are neurotoxic and have been demonstrated to increase the risk of PN. [9][10][11] However, other studies have shown that d-drug ARV do not increase the risk or severity of DSP. 6,7,12 It is not clear whether mitochondrial mechanisms are responsible for d-drug ARV neurotoxicity.…”
mentioning
confidence: 96%
“…[9][10][11] However, more recent trials have shown that d-drug ARV did not add further risk to the occurrence of HIVassociated PN. [5][6][7]12 Therefore, it is not clear how best to predict which patients are at highest risk for the development of DSP while being treated with d-drug ARV regimens.…”
mentioning
confidence: 99%